Academic Engagement in Sport for Development: Niche or Growing Community? - Moustakas Louis; Petry Karen; Bauer Katrin (Sciendo, 2023)
Over the last two decades, the sport for development (SFD) sector has grown significantly, and there has been a concurrent increase in research and educational activities to support the field. In particular, academic institutions are taking a more significant role, contributing to a growing body of literature and developing numerous SFD-specific courses. Despite these initiatives and the important role assigned to academia, academic activities related to SFD have remained fragmented along geographic or disciplinary lines, and our knowledge of academic activities and collaborations is limited and focused on actors in the Global North. This study seeks to address these gaps and, through an international survey of academic institutions, aims to (1) establish the teaching, research and partnership activities within and between academic institutions around the globe; and (2) identify challenges and inform solutions for greater cooperation within and between academic institutions in the SFD context. Overall, our results show that the SFD is a highly multidisciplinary field involving institutions from a perhaps wider-than-expected range of countries. However, funding, support and recognition of SFD and associated academic actors, especially in the Global South, remains limited. To conclude, we propose potential ways forward to address some of these issues.